Institutional Ownership as Boundary Condition of Green Innovation and Firm Value in ASEAN - Wiara Sanchia Grafita Ryana Devi; Ikaputera Waspada; Nugraha Nugraha; Maya Sari; Rengga Madya Pranata (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the effect of financial performance on firm value with Green Innovation as a moderating variable and investigates the boundary role of Institutional Ownership as a second moderator (moderated moderation framework) in the ASEAN energy sector. Research Methodology: A balanced panel dataset of 76 energy sector companies listed in six ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines, Vietnam, and Singapore) for the period 2019–2024, yielding 456 observations, was utilized. Data were collected from Refinitiv. Results: Without green innovation, financial performance ROA has a significant negative effect on firm value (? = ?0.0713, p = 0.0484). Green innovation significantly and positively moderated this relationship (? = +0.1125, p = 0.0035). Institutional ownership is confirmed to be a critical boundary condition (? = +0.1565, p = 0.0000). Green innovation signals are activated only when institutional ownership exceeds 70.73%. Conclusions: This study confirms the profitability paradox in the ASEAN energy sector: high profitability driven by geopolitical shocks does not enhance firm value unless it is accompanied by green innovation. Institutional ownership functions as an essential activation point that enables markets to interpret and value sustainability efforts. Limitations: The sample is confined to six ASEAN countries and relies on Refinitiv and sustainability reports, which may not fully capture the differences between strategic and substantive green innovations. Contributions: This study extends Signaling Theory by introducing institutional ownership as a signal receiver capacity', demonstrating that green innovation value creation requires a critical concentration of institutional monitoring (threshold: 70.73%).